Researching and reorienting mentorship practices to empower the success of Indigenous Australian young people - Matilda Harry; Michelle Trudgett; Susan Page; Rebekah Grace (The Australian Journal of Indigenous Education, 2023)
This article discusses mentorship provided to Indigenous Australian secondary school leavers. The authors suggest that although current scholarship in the field is insightful, there is a dearth focussing on mentorship provided during the post-secondary school transitional phase. Also, much literature problematizes Indigenous mentees and is contextually bound to individual programs, singular communities or cohorts. Although governments, industries, communities and further education providers have funded and facilitated many mentorship programs across the nation, little systemic or institutional impact has been made. Current data demonstrates a continuous downward trajectory in the full engagement of Indigenous Australian secondary school leavers, that is, those who are full-time working, studying or both studying and working (Australian Bureau Statistics, 2021; Department of Prime Minister and Cabinet, 2018). This is concerning as the post-secondary school transitional phase is cited as a critical stage for combating or embedding inequities young Indigenous Australians often endure intergenerationally (O’Shea, McMahon, Priestly, Bodkin-Andrews & Harwood, 2016). By centring national and international First Nations scholars the authors argue for reconceptualisations of Indigenous mentee success through Indigenous ontological lenses and reorientations of mentorship frameworks towards approaches which strengthen young peoples’ connections with culture, community, Elders and Country.